Reducing Old Age and Economic Vulnerabilities : Why Uganda Should Improve its Pension System - World Bank (Washington, DC, 2014)
This is the fourth edition of the Uganda Economic Update series. As with previous editions, this update first provides information related to the current state of the economy before focusing on a particular subject of importance. The special focus of this issue concerns how pensions can reduce vulnerabilities at both individual and macroeconomic levels. The Ugandan economy has continued the process of recovery, growing by 5.9 percent during the first half of FY2013 and FY2014 amidst droughts, disruptions related to civil unrest in South Sudan, and aid cuts. Eight consecutive quarters of positive growth since the slump in FY2011 and FY2012 confirm that the economy has returned on the strong growth path and may reach a rate of growth of 6.0 percent per annum in FY2013 and FY2014. The positive outlook is subject to risks, key among which will be those emanating from its fiscal management regime due to continuous low revenue collection and reduction of aid to Uganda; increased spending pressures in the advent of the 2016 elections, and accelerating public investments amidst gaps in public investment efficiency. In addition, given its recently increased dependency on the South Sudan market for its exports, the protracted crisis in South Sudan could have severe consequences to the Ugandan economy. In that context, a coherent policy of social protection, including for the elderly, can promote social transformation and accelerate economic development. An effective social protection system is needed to protect vulnerable groups from negative shocks such as loss of employment, death of bread winner, or bad weather. Achieving the vision of a transformed Uganda means addressing vulnerabilities at both individual and at country levels. Uganda is already taking steps to start building an effective pension system, but challenges remain in ensuring transparent and proper governance of the pension funds; achieving efficiency objectives, building up the institutional capacity, and managing the fiscal pressures due to expenses to existing pensions and the new public pension scheme at the same time. Well designed and managed pension systems can contribute significantly to the country's ongoing transformation.